Characterisation of the mechanical properties of infarcted myocardium in the rat under biaxial tension and uniaxial compression. (October 2016) - Sirry, Mazin S.; Butler, J. Ryan; Patnaik, Sourav S.; Brazile, Bryn; Bertucci, Robbin; Claude, Andrew; McLaughlin, Ron; Davies, Neil H.; Liao, Jun; Franz, Thomas
Abstract: Understanding the passive mechanical properties of infarcted tissue at different healing stages is essential to explore the emerging biomaterial injection-based therapy for myocardial infarction (MI). Although rats have been widely used as animal models in such investigations, the data in literature that quantify the passive mechanical properties of rat heart infarcts is very limited. MI was induced in rats and hearts were harvested immediately (0 day), 7, 14 and 28 days after infarction onset. Left ventricle anterioapical samples were cut and underwent equibiaxial and non equibiaxial tension followed by uniaxial compression mechanical tests. Histological analysis was conducted to confirm MI and to quantify the size of the induced infarcts. Infarcts maintained anisotropy and the nonlinear biaxial and compressive mechanical behaviour throughout the healing phases with the circumferential direction being stiffer than the longitudinal direction. Mechanical coupling was observed between the two axes in all infarct groups. The 0, 7, 14 and 28 days infarcts showed 438, 693, 1048 and 1218 kPa circumferential tensile moduli. The 28 day infarct group showed a significantly higher compressive modulus compared to the other infarct groups ( p =0.0060, 0.0293, and 0.0268 for 0, 7 and 14 days groups). Collagen fibres were found to align in a preferred direction for all infarct groups supporting the observed mechanical anisotropy. The presented data are useful for developing material models for healing infarcts and for setting a baseline for future assessment of emerging mechanical-based MI therapies. Highlights: Rat myocardial infarcts exhibit mechanical anisotropy up to 28 days post-infarction. Infarcts are stiffer in circumferential than in longitudinal direction. Mechanical anisotropy is supported by collagen fibre orientation in infarcts. Infarcts exhibit in-plane mechanical coupling. Circumferential and compressive stiffness of healing infarcts increases with time.